2022
DOI: 10.1098/rstb.2021.0124
|View full text |Cite
|
Sign up to set email alerts
|

Nature-based solutions for atoll habitability

Abstract: Atoll societies have adapted their environments and social systems for thousands of years, but the rapid pace of climate change may bring conditions that exceed their adaptive capacities. There is growing interest in the use of ‘nature-based solutions' to facilitate the continuation of dignified and meaningful lives on atolls through a changing climate. However, there remains insufficient evidence to conclude that these can make a significant contribution to adaptation on atolls, let alone to develop standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Whilst this short period spans the personal experience of atoll residents who have witnessed these changes, and who may have undertaken local adaptations to reduce impacts 48 , we have shown that the magnitude of recent island movements has been dwarfed by those that have occurred over the previous centuries. Significantly, while there has been recent enthusiasm for creating nature-based solutions, that work with environmental processes, to support climate change adaptation in reef island settings 49 , many proposed solutions still rely on a temporally short-sighted understanding of system dynamics, rely on vegetation solutions or technological interventions, and ignore landform dynamics. Such considerations need to be based on more than observations over recent decades and should be contextualised where possible, against the longer-term dynamics of island landforms.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this short period spans the personal experience of atoll residents who have witnessed these changes, and who may have undertaken local adaptations to reduce impacts 48 , we have shown that the magnitude of recent island movements has been dwarfed by those that have occurred over the previous centuries. Significantly, while there has been recent enthusiasm for creating nature-based solutions, that work with environmental processes, to support climate change adaptation in reef island settings 49 , many proposed solutions still rely on a temporally short-sighted understanding of system dynamics, rely on vegetation solutions or technological interventions, and ignore landform dynamics. Such considerations need to be based on more than observations over recent decades and should be contextualised where possible, against the longer-term dynamics of island landforms.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the continued habitation of atoll islands that naturally adjust to sea level rise through overwash-induced accretion, flexibility and adaptability are required of both the island infrastructure and its communities. Flexible infrastructure can be achieved through a variety of measures, such as building houses on stilts (Esteban et al, 2019), flood protection at the household level (raising doorstep levels, implementing local flood walls; Brown et al, 2020), and nature-based coastal protection measures (Barnett et al, 2022). Social adaptation is also a key factor in allowing for natural island dynamics.…”
Section: Morphological Response Of Reef Profiles With Adaptationmentioning
confidence: 99%
“…Constraints to living on such a naturally-adjusting island are also considerable and include, amongst others, lack of space for the island to migrate to, resilience of island communities to episodic and potentially hazardous flood events, adaptability of current island infrastructure and housing, threats to fresh water supply and adverse impacts on agriculture. At the same time, early-warning systems (Winter et al, 2020) and nature-based coastal protection measures (Barnett et al, 2022) can help facilitate island communities to sustainably live on a dynamic and frequently-flooded island. Adaptation measures, including nature-based solutions such as reef restoration and enhancing beach vegetation, may help atoll islands to gradually adjust to SLR.…”
Section: Introductionmentioning
confidence: 99%